Development of an Educational Game ‘Petualangan Ryna’ as a Learning Media for Geometric Transformations in Junior High School - Ardiansyah, Izza; Sisworo, Sisworo; Purwanto, Purwanto (Universitas Suryakancana, 2025)
The teaching of geometric transformations in junior high school continues to face several challenges, especially regarding the topics of translation and reflection, which require a strong understanding of visual and spatial concepts. This issue was identified at a junior high school in Pasuruan Regency, where diagnostic tests and classroom observations revealed low student comprehension and a lack of interactive instructional media. In response, this study aimed to develop an educational game titled Petualangan Ryna di Desa yang Hilang using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The goal was to produce a valid, practical, and effective learning tool. The research involved seventh-grade students as participants, with data collected through expert validation, post-tests, and student response questionnaires. The results indicated that the developed game and assessment instruments were valid, the game was practical to use, and it effectively improved students’ understanding of geometric transformations. Therefore, Petualangan Ryna di Desa yang Hilang is suitable for classroom use as an innovative learning media that enhances engagement and conceptual understanding through contextual and visual exploration.